2021
DOI: 10.52547/nfsr.8.2.5
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Food Security Statuses in Afghan Refugees in Iran

Abstract: Background and Objectives:Refugees are often further susceptible to food insecurity in host countries. This study was carried out to review food insecurity statuses of Afghan refugees in Iran. Materials and Methods:A comprehensive search was carried out using keywords of "food insecurity", "food security", "Iran", "Afghan", "immigrant" and "refugee" in English databases, including Scopus, Web of Science, PubMed and Google Scholar, as well as Persian databases, including Scientific Information Database, Noor, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The food insecurity of refugees in Iran has been documented in several studies. It is reported that about 80% of them face some aspect of food insecurity that puts them at risk of obesity ( 18 , 19 , 38–40 ). In illegal refugees, food insecurity is exacerbated ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The food insecurity of refugees in Iran has been documented in several studies. It is reported that about 80% of them face some aspect of food insecurity that puts them at risk of obesity ( 18 , 19 , 38–40 ). In illegal refugees, food insecurity is exacerbated ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that about 80% of them face some aspect of food insecurity that puts them at risk of obesity ( 18 , 19 , 38–40 ). In illegal refugees, food insecurity is exacerbated ( 38 ). The pattern of obesity in Iranian refugees is very similar to families with low social class in Iran, and it is similar to Iranians in their living area ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation